Production and simulated digestion of high-load beads containing Schizochytrium oil encapsulated utilizing prilling technique - Beltrame, Gabriele; Damerau, Annelie; Ahonen, Eija; Mustonen, Sari A.; Adami, Renata; Sellitto, Maria Rosaria; Del Gaudio, Pasquale; Linderborg, Kaisa M. (Elsevier, 2025)
The oil from the heterotroph Schizochytrium is a rich source of n-3 PUFA, particularly DHA, and therefore highly susceptible to oxidation. The present work reports the first application of coaxial prilling for the protection of this oil through microencapsulation. After process optimization, core-shell microparticles were produced with calcium or zinc alginate at different concentrations. Encapsulates were analyzed in their tocopherol and PUFA content. Prilling lowered the earlier but had little effect on the latter. Microcapsules coated with calcium alginate (1 % and 1.75 %) had higher oil load and encapsulation efficiency and were therefore submitted to in vitro digestion together with a simulated meal. Digesta were also analyzed with HPLC-qTOF and 1H NMR and compared to undigested encapsulates. While 1 % calcium shell granted lower oil release and protection from oxidation in the simulated gastrointestinal tract, chromatographic and spectroscopic data of digesta showed higher presence of lipid digestion products.